Recent progress on the functionalization of white phosphorus in China - Huangfu, Xinlei; Wang, Zhongzhen; Chen, Yu; Wei, Junnian; Liu, Wei; Zhang, Wen-Xiong (National science review, 2024)
Direct synthesis of organophosphorus compounds from white phosphorus represents a significant but challenging subject, especially in the context of ongoing efforts to comprehensively improve the phosphorus-derived chemical industry driven by sustainability and safety concerns. China is the world's largest producer of white phosphorus, creating a significant demand for the green transformation of this crucial feedstock. This review provides an overview of advancements in white phosphorus activation by Chinese research teams, focusing on the direct construction of P‒C/N/O/S/M bonds from white phosphorus. Additionally, we offer some insights into prospective directions for the activation and transformation of white phosphorus in the future. This review paper aims to attract more researchers to engage in this area, stimulating follow-up exploration and fostering enduring advances. This review outlines the advances of white phosphorus chemistry in China and offers insights into future developments, serving as a window to comprehend the contributions from Chinese researchers in this field.